On the numerical solution of the far field refractor problem. (July 2017) - De Leo, Roberto; Gutiérrez, Cristian E.; Mawi, Henok
Abstract: The far field refractor problem with a discrete target is solved with a numerical scheme that uses and simplify ideas from Caffarelli et al. (1999). A numerical implementation is carried out and examples are shown.